2014
DOI: 10.1037/a0035324
|View full text |Cite
|
Sign up to set email alerts
|

Race and bicultural socialization in the Netherlands, Norway, and the United States of America in the adoptions of children from India.

Abstract: A cross-national sample of 622 internationally adopted children from India with White parents in The Netherlands (n = 409), Norway (n = 146), and the United States (n = 67) was used to contrast country-specific bicultural socialization (BCS) practices among families of transracial intercountry adoption. The 3 countries vary in their degrees of minority (US > Netherlands > Norway) and Indian populations (US > Norway > Netherlands). The current study examined parental survey trends among BCS practices, children'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Consistent with these qualitative studies, a handful of quantitative studies focusing on racial discrimination among internationally adopted children in Spain (Reinoso, Juffer, & Tieman, 2013), the Netherlands, Norway, and the United States (Riley-Behringer, Groza, Tieman, & Juffer, 2014) have shown the prevalence of racial discrimination, especially among nonwhite adoptees. The most compelling message of these studies is that perceived discrimination is harmful for social and psychological well-being, and that to deal with it adoptees need to develop a broad range of coping strategies to respond to the diverse situations in which they may perceive discrimination.…”
mentioning
confidence: 81%
“…Consistent with these qualitative studies, a handful of quantitative studies focusing on racial discrimination among internationally adopted children in Spain (Reinoso, Juffer, & Tieman, 2013), the Netherlands, Norway, and the United States (Riley-Behringer, Groza, Tieman, & Juffer, 2014) have shown the prevalence of racial discrimination, especially among nonwhite adoptees. The most compelling message of these studies is that perceived discrimination is harmful for social and psychological well-being, and that to deal with it adoptees need to develop a broad range of coping strategies to respond to the diverse situations in which they may perceive discrimination.…”
mentioning
confidence: 81%
“…Parent Role elements may be influenced by societal values and messages (E1). A cross-national study of TRA families from The Netherlands, Norway, and the United States found that US TRA families encountered the most adoption and racial discrimination; US parents also were the mostly likely to be worried about others’ negative reactions (A1) and value cultural socialization (A2) (Riley-Behringer, Groza, Tieman, & Juffer, 2014). In a study of US parents with internationally adopted children, parents of Asian and Latin American children reported higher perceived discrimination (A1) than did parents of Eastern European children; notably, in families where the phenotypic differences were more evident, parents perceived more bias (A1) (Lee & Minnesota International Adoption Project [MIAP], 2010).…”
Section: Process-oriented Transactional System Of Ethnic–racial Socializationmentioning
confidence: 99%
“…A last potential explanation of our findings may be related to varying post-adoption experiences of the international adoptees, including possibly different trajectories of peer-group identification and integration of adoptees from specific countries in the Netherlands. For example, some studies have focused on the intricacies of living in a multi-ethnic adoptive family or experiencing racial discrimination outside the adoptive home (e.g., Basow, Lilley, Bookwala, & Gillicuddy-DeLisi, 2008;Mohanty, 2013;Riley-Behringer, Groza, Tieman, & Juffer, 2014), but it is yet unknown whether these processes and experiences are largely similar or rather diverse for adoptees from different countries of origin.…”
Section: Heterogeneity In Adopteesmentioning
confidence: 99%